2015
DOI: 10.1080/0376835x.2015.1010715
|View full text |Cite
|
Sign up to set email alerts
|

Is small beautiful? Understanding the contribution of small businesses in township tourism to economic development

Abstract: The increased importance attached by policy-makers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…It has been noted elsewhere that the very limited understanding of township tourism business behaviour is a major impediment for policy-makers (Koens and Thomas, 2015). In their recent comprehensive review of the field, Thomas, Shaw and Page (2011) note that small businesses in tourism remain generally under-theorised and under-researched.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted elsewhere that the very limited understanding of township tourism business behaviour is a major impediment for policy-makers (Koens and Thomas, 2015). In their recent comprehensive review of the field, Thomas, Shaw and Page (2011) note that small businesses in tourism remain generally under-theorised and under-researched.…”
Section: Introductionmentioning
confidence: 99%
“…The present study, while exploratory in nature, contributes to the understanding of communities' perceptions of tourism impacts in pilgrimage trails, as well as to suggest potential alternatives towards a small scale, slower tourism development in the areas that capitalizes in the characteristics of pilgrimage tourism. This approach can be an alternative development strategy (Koens and Thomas 2015) in contrast to recent cases of over-tourism (Hagi 2017;Seraphin, Sheeran and Pilato 2018). As the residents seem to prefer an overall small development that favors close interactions with visitors, a balance in development may be of utmost importance for sustainable tourism policies.…”
Section: Discussionmentioning
confidence: 99%
“…The research revealed tension among various entities that are involved in urban tourism. While the involvement of small local enterprises is beneficial, they are restricted in their actions by conflicts of interest, the lack of trust, limited social networks, and poor involvement in urban communities [98].…”
Section: Trust and Social Network In Tourismmentioning
confidence: 99%